HERV-K-T47D-related long terminal repeats mediate polyadenylation of cellular transcripts - Baust, Corinna; Seifarth, Wolfgang; Germaier, Herbert; Hehlmann, Rüdiger; Leib-Mösch, Christine (Genomics, 2000)
The human genome harbors thousands of long terminal repeats (LTRs) that are derived from endogenous retroviruses and contain elements able to regulate the expression of neighboring cellular genes. We have investigated the ability of human endogenous retroviral (HERV)-K LTRs to provide transcriptional processing signals for nonviral sequences. Four chimeric cDNA clones isolated from a cDNA library derived from the human cell line T47D were found to be polyadenylated within an HERV-K-T47D-related LTR. Two transcripts containing an as yet unknown cellular sequence were probably derived from the same genomic locus but their 3′ ends were processed at different positions of the LTR. Structural analysis of the polyadenylation site suggests RNA stem-loop structures similar to the HTLV-1 Rex responsive element that bring the two remote AAUAAA and GU-rich elements into the spatial juxtaposition necessary for correct 3′ end processing. The cellular part of the third chimeric clone shows significant homology to an exon of the human tyrosine phosphatase 1 gene, although oriented in the antisense direction compared to the adjacent LTR. Furthermore, we found that the 3′ untranslated region of the human transmembrane tyrosine kinase gene FLT4 is probably derived from a partial HERV-K-T47D LTR sequence. Taken together, our data suggest that LTRs of the HERV-K-T47D family display biological function by mediating polyadenylation of cellular sequences.